The effect of a nanofiber-hydrogel composite on neural tissue repair and regeneration in the contused spinal cord. (July 2020) - Li, Xiaowei; Zhang, Chi; Haggerty, Agnes E.; Yan, Jerry; Lan, Michael; Seu, Michelle; Yang, Mingyu; Marlow, Megan M.; Maldonado-Lasunción, Inés; Cho, Brian; Zhou, Zhengbing; Chen, Long; et al.
Abstract: An injury to the spinal cord causes long-lasting loss of nervous tissue because endogenous nervous tissue repair and regeneration at the site of injury is limited. We engineered an injectable nanofiber-hydrogel composite (NHC) with interfacial bonding to provide mechanical strength and porosity and examined its effect on repair and neural tissue regeneration in an adult rat model of spinal cord contusion. At 28 days after treatment with NHC, the width of the contused spinal cord segment was 2-fold larger than in controls. With NHC treatment, tissue in the injury had a 2-fold higher M2/M1 macrophage ratio, 5-fold higher blood vessel density, 2.6-fold higher immature neuron presence, 2.4-fold higher axon density, and a similar glial scar presence compared with controls. Spared nervous tissue volume in the contused segment and hind limb function was similar between groups. Our findings indicated that NHC provided mechanical support to the contused spinal cord and supported pro-regenerative macrophage polarization, angiogenesis, axon growth, and neurogenesis in the injured tissue without any exogenous factors or cells. These results motivate further optimization of the NHC and delivery protocol to fully translate the potential of the unique properties of the NHC for treating spinal cord injury.